The BASIDIN effector of the fungus Moniliophthora perniciosa promotes positive effects on the seed germination and seedlings development of Lactuca sativa - Farias, Keilane Silva; Ferreira, Monaliza Macêdo; De Oliveira, Ivina Barbosa; Dalio, Ronaldo José Durigan; Pirovani, Carlos Priminho (Frontiers in Plant Science, 2025)
Plant resistance inducers that activate plant defense mechanisms may be useful in reducing agrotoxic use. Lettuce is among the most economically important leafy vegetable crops in the world. Since lettuce propagates through seeds, the use of high-quality seeds is extremely important for establishing the crop. Several studies have demonstrated the potential of alternative methods of seed treatment with the aim of increasing productivity. Based on this premise, we tested the effect of the rBASIDIN effector regarding its ability to induce germination and physiological changes in lettuce seedlings through seed treatment. The seeds were treated for 30 min by soaking with 50 µg mL-1, 75 µg mL-1 and 100 µg mL-1 of the recombinant effector protein rBASIDIN. Seeds treated with distilled water and 10 mmol of Tris-HCl served as controls. The physiological parameters evaluated were germination percentage at 4 and 7 days, seedling length (aerial part and root), dry and fresh mass, electrical conductivity, and enzymatic activity. Seeds treated with 50 and 75 µg mL-1 of rBASIDIN germinated earlier than the controls. Treatment with rBASIDIN at a concentration of 50 µg mL-1 resulted in seedlings with an average root length of 1.51 cm, while the average lengths of the controls (H2O and buffer) were 0.86 and 0.70 cm respectively. Seed treatment with rBASIDIN caused an increase in the fresh and dry weight of the plants. The lowest electrolyte leakage was detected in seeds treated with the three concentrations of rBASIDIN compared to the controls. Regarding the activity of defense enzymes, seedlings treated with rBASIDIN at lower concentrations showed higher chitinase and β-glucanase activity compared to the controls. The results indicated that the rBASIDIN effector plays an important signaling role in lettuce seeds, since small doses are already sufficient to induce changes in physiological parameters to obtain more vigorous plants.